PERAN PENDIDIKAN AGAMA ISLAM DALAM MEMBENTUK KARAKTER SISWA - Syah Rani Maha (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2023)
Morals are behavior that is clearly visible, both in words and deeds, which is motivated by encouragement because of Allah. However, there are also many aspects related to attitudes or inner thoughts, such as initial morals which are related to various aspects, namely patterns of behavior towards God, fellow humans, and patterns of behavior towards nature. Moral issues become a barometer of a person's high or low status. This is in accordance with the words of the Prophet Muhammad SAW: